Hospital Management: Doctors Role and Responsibilities - BHULLAR, DS (GMC Patiala Journal of Research and Medical Education, 2022)
The word Hospital has got its origin from the Latin word Hospes which means guest i.e. a place where a patient is accommodated as a guest and should be treated as a guest with dignity and honor. In context of the Indian culture, wherein a guest is taken akin to God, services provided to an ailing patient are not less than worshiping God. Hospital is a complex organisation wherein the doctors together along with people of different expertise and skills work to fulfil the common goal of care and cure of the ailing patient. Apart from treatment of their patients, the doctors today have a bigger role to play in the management of hospital affairs and other important functions for them as professionals which include training and education of the undergraduate and postgraduate medical students, nurses and paramedical, health promotion and prevention of diseases, medical research and rehabilitation work and heath awareness and education to the community.